Effect of 6 years of continous cultivation by no-till or pudding systems on soil properties and rice yield of a clay soil - Lal, R. (1986)
Rice response to no-till and puddling methods of seedbed preparation were evaluated for four levels of N application: 0, 50, 100 and 150 kg ha−1 N. Growing 11 consecutive crops of rice on an Aeric Tropaquent in southwestern Nigeria produced mean grain yields of 3.5 and 5.5 t ha−1 with no-till and 3.9 and 5.6 t ha−1 with puddling systems at 0 and 150 kg ha−1 N per crop, respectively. In general, puddled treatments yielded more at a low level of N than no-till plots and the rice grain yields were lower for the second than the first growing seasons. The mean organic carbon content measured after 6 years in the 0–5-cm layer was 2.2. and 1.7% (w/w), respectively, for the no-till and the puddled seedbeds. In the 5–10-cm layers, however, the no-tilled soil contained less organic carbon than the puddled, viz. 1.1 and 1.7% (w/w), respectively. The mean bulk densities of no-till and puddled soils were 0.96 and 1.24 Mg m−3 for the 0–1-cm layer and 1.07 Mg m−3 for the 1–2-cm layer. The clay content of the 0–1-cm layer was higher in the puddled (36.6%, w/w) than in the no-till treatment (34.0%, w/w). The surface 0–1- and 1–2-cm layers of the no-till system retained significantly more water at water potentials from 3 kPa to 1.5 MPa than the puddled soil, viz. 66.5 vs. 51.1% (w/w) for the 0–1-cm depth and 51.1 vs 49.5% (w/w) for the 1–2-cm depth at 3 kPa and 24.7 vs. 21.5% (w/w) for the 0–1-cm depth and 20.5 vs 20.2% (w/w) for the 1–2-cm depth at 1.5 MPa, respectively. The differences in soil moisture retention in favor of no-till were more pronounced at high than at low soil moisture potentials.